Respon Pertumbuhan Dan Produksi Tanaman Tomat (Solanum Lycopersicum) Dengan Pemberian Bokashi Tithonia (Tithonia Diversifolia) - Andina Widya Sari (UNIVERSITAS NEGERI PADANG, 2017)
Tomato (Solanum lycopersicum) is a vegetable that belongs to the family Solanaceae. Seeing the potential in the domestic and overseas large enough, then the tomato business has a bright prospect. Tomatoes are needed by humans to meet their needs. This is due to the nutritional content of tomato fruit consisting of vitamins and minerals that are very useful for maintaining health and preventing disease, to improve the productivity of tomatoes is done by using fertilizers that Tithonia Bokashi fertilizer. This study aimed to evaluate the response of growth and yield of tomato (Solanum lycopersicum) by giving Bokashi Tithonia (Tithonia diversifolia). This type of research is an experimental study. The study design used was a completely randomized design (CRD) with 6 treatments and 4 replications. The treatments given are dose bokashi Tithonia A = 0 g / polybag, B = Urea, C = 200 g / polybag, D = 400 g / polybag, E = 600 g / polybag, F = 800 g / polybag, parameters tomatoes observed is high, the amount of tomatoes and tomato weight. Data were analyzed using ANOVA and a further test DNMRT at 5% level. Based on the research results show that the tomato plant height, number of tomatoes and tomato fruit weight was significantly different from the provision of Bokashi Tithonia. Dose of 800g / polybag best in improving the response to the growth and production of tomatoes. Key word : Bokashi, Tithonia diversifolia, Solanum lycopersicum